2008
DOI: 10.1248/jhs.54.645
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of Kotahla Himbutu (Salacia reticulata) Stems Promotes Oxygen Comsumption and Supresses Body Fat Accumulation in Mice

Abstract: Kothala himbutu (KT) is a traditional medicinal plant used in treating diabetes in Ayurvedic medicine. We investigated the effect of the aqueous extract of KT stems (KTE) on energy expenditure in normal mice. Male C57BL/6J mice (n = 28) were divided into 4 groups depending on the type of diet they were fed for 9 weeks: normal (N) diet group (N: 13.8% energy in the form of fat), high-fat (HF) diet group (HF: 53.0% energy in the form of fat), 0.1% freeze-dried KTE (KTED)-supplemented N diet group (N+KTED), and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Also, S. reticulata significantly suppressed the accumulation of mesenteric adipose tissue in the TSOD mice but showed no effect in the TSNO mice. The significant suppression of adipose tissue accumulation by S. reticulata has been reported previously [2,5,11,22], and a similar result was obtained in this study. It is known that adipocyte hypertrophy changes adipocytokine secretion levels and is involved in the onset of various metabolic disease symptoms including insulin resistance [1].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Also, S. reticulata significantly suppressed the accumulation of mesenteric adipose tissue in the TSOD mice but showed no effect in the TSNO mice. The significant suppression of adipose tissue accumulation by S. reticulata has been reported previously [2,5,11,22], and a similar result was obtained in this study. It is known that adipocyte hypertrophy changes adipocytokine secretion levels and is involved in the onset of various metabolic disease symptoms including insulin resistance [1].…”
Section: Discussionsupporting
confidence: 93%
“…It has previously been reported that S. reticulata and S. oblonga have antiobesity, antidiabetic, and lipid metabolism abnormality-alleviating effects [2,6,7,11,22]. Data represent the mean ± SD values (n = 9-10)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The roots are acrid, bitter, thermogenic, urinary, astringent, anodyne, anti-inflammatory and haemorrhoids [8]. The roots and stem have been widely used in treating diabetes and obesity, gonorrhoea, skin diseases and rheumatism [9,10]. It is also beneficial for the prevention of diabetes; obesity and lowers the lipid peroxide level ofthe kidney [11].…”
Section: Introductionmentioning
confidence: 99%